Photodissociation dynamics of OCS at 248 nm: the S((1)D(2)) atomic angular momentum polarization. - Brouard, M; Green, A; Quadrini, F; Vallance, C (2007)
The dissociation of OCS has been investigated subsequent to excitation at 248 nm. Speed distributions, speed dependent translational anisotropy parameters, angular momentum alignment, and orientation are reported for the channel leading to S((1)D(2)). In agreement with previous experiments, two product speed regimes have been identified, correlating with differing degrees of rotational excitation in the CO coproducts. The velocity dependence of the translational anisotropy is also shown to be in agreement with previous work. However, contrary to previous interpretations, the speed dependence is shown to primarily reflect the effects of nonaxial recoil and to be consistent with predominant excitation to the 2 (1)A(') electronic state. It is proposed that the associated electronic transition moment is polarized in the molecular plane, at an angle greater than approximately 60 degrees to the initial linear OCS axis. The atomic angular momentum polarization data are interpreted in terms of a simple long-range interaction model to help identify likely surfaces populated during dissociation. Although the model neglects coherence between surfaces, the polarization data are shown to be consistent with the proposed dissociation mechanisms for the two product speed regimes. Large values for the low and high rank in-plane orientation parameters are reported. These are believed to be the first example of a polyatomic system where these effects are found to be of the same order of magnitude as the angular momentum alignment.